2019
DOI: 10.1098/rspb.2019.1929
|View full text |Cite
|
Sign up to set email alerts
|

Specialized sledge dogs accompanied Inuit dispersal across the North American Arctic

Abstract: Domestic dogs have been central to life in the North American Arctic for millennia. The ancestors of the Inuit were the first to introduce the widespread usage of dog sledge transportation technology to the Americas, but whether the Inuit adopted local Palaeo-Inuit dogs or introduced a new dog population to the region remains unknown. To test these hypotheses, we generated mitochondrial DNA and geometric morphometric data of skull and dental elements from a total of 922 North American Arctic dogs and wolves sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 45 publications
2
60
0
1
Order By: Relevance
“…Modern and ancient dogs are grouped into four major haplogroups (A–D), and two minor haplogroups (E–F) (e.g. [ 24 , 25 ]). Haplogroup A is the most diverse, including most dog breeds [ 9 ] and the PCD subclade [ 11 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern and ancient dogs are grouped into four major haplogroups (A–D), and two minor haplogroups (E–F) (e.g. [ 24 , 25 ]). Haplogroup A is the most diverse, including most dog breeds [ 9 ] and the PCD subclade [ 11 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The well-preserved remains of a young puppy, including a woven grass collar and leash, were found wrapped in grass mat and buried outside the entry of a side room in the Phase II house. Skeletal and DNA studies of the Nunalleq dogs are ongoing but have already indicated connections with dog populations elsewhere in the north, at precontact Inuit and other Thule-era sites (Ameen et al 2019).…”
Section: Faunal Remainsmentioning
confidence: 99%
“…Most striking is that the few and geographically distant source regions of metal, its high frequency of use, and the lack of mobility technologies common in Inuit context—such as dog sleds (Ameen et al 2019; Morey and Aaris-Sørensen 2002) and large watercraft (Mary-Rousselière 1979)—do not seem to have limited the amount of inter-group interaction among the Late Dorset (Appelt et al 2016; Desrosiers 2017; Maxwell 1985; Odess 1998). Using a least-cost path analysis to estimate travel times between native copper sources and sites with existing copper objects, Pike and colleagues (2019) demonstrate that most sites are over 112 hours of travel (i.e., 14 eight-hour days) in the warmer months, with roughly 30% of sites requiring more than 200 hours of travel (i.e., 25 eight-hour days).…”
Section: Metal Use As Interaction Networkmentioning
confidence: 99%